2015
DOI: 10.1111/dote.12338
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the potential use of microRNAs as a novel class of biomarkers in esophageal cancer

Abstract: MicroRNAs (abbreviated miRNAs) have been demonstrated to be involved in tumorigenesis and cancer development and proposed as promising biomarkers in cancer diagnosis. Numerous studies have observed the aberrant expression of miRNAs in esophageal cancer. However, there are some discrepant results. Thus, we conducted this meta-analysis to identify the overall accuracy of miRNAs in the diagnosis of esophageal cancer. A comprehensive literature search was conducted in PubMed and other databases using combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…Concerning ESCC, several studies have indicated the potential value of circulating miRNAs in diagnosis of the disease [20]. But most studies only focused on some specific miRNAs, few studies explored circulating miRNA profiles using the comprehensive array-based approach in ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning ESCC, several studies have indicated the potential value of circulating miRNAs in diagnosis of the disease [20]. But most studies only focused on some specific miRNAs, few studies explored circulating miRNA profiles using the comprehensive array-based approach in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have opened up a new and promising filed in the screening and monitoring of cancer patients. Since the first study on the levels of serum miRNAs in ESCC patients was reported in 2010 by Zhang et al [19], several studies have investigated the differential expression of circulating miRNAs and explored the potential application of the biomarkers in ESCC [20]. However, the results were not consistent between the studies partly due to different research methods and tested populations.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are a recently discovered class of small (19)(20)(21)(22)(23)(24) nucleotides) endogenous non-coding oligonucleotides that regulate gene expression at the post-transcriptional level [1][2][3]. They play a crucial role in regulation of physiological and pathological processes and some miRNAs have been described as associated with distinct clinical characteristics, such as diagnosis or disease activity [4][5][6][7][8][9]. For these reasons, miRNAs are attractive as potential biomarkers for the diagnosis, prognosis, disease activity and severity of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis [54] including 27 studies reported that circulating miRNAs with a combined AUC of 0.87 could be used as a biomarkers for early diagnosis of ESCC. MiRNAs presented in blood or other tissue fluid in a stable form [55]. Therefore, circulating miRNAs can be candidates for noninvasive diagnosis of ESCA.…”
Section: Discussionmentioning
confidence: 99%